OPTIMIZING LİVESTOCK PRODUCTIVITY THROUGH INCREASED FEED PRODUCTION IN WEST MANGGARAI - Foeh, Nancy; Detha, Annytha; Ndaong, Nemay; Datta, Frans Umbu; Maranatha, Grace (International Journal of Community Service Learning, 2020)
The Aims of this activity to optimize livestock productivity through the independence and adequacy of animal feed, enhancing the beauty of the area through the use of livestock waste which has a significant impact on increasing livestock farmers' income in Nggorang Desa, Komodo District, West Manggarai, NTT. An initial survey to determine the location of the training venue was conducted in October 2018 in Nggorang Village, Komodo District, West Manggarai. Activities to introduce grazing land will be carried out on August 22-25, 2019 which is located in the Meeting Hall of the Village office in Nggorang. Participants in the extension activity were attended by 20 people from the cattle group of Nggorang Village, Komodo District, West Manggarai Regency. The approach method offered in the form of education and training is accompanied by the creation of a pilot model and assistance as well as evaluation monitoring. Training activities about Bokashi feed and waste processing technology and the application of integrated grazing land significantly increase farmers' understanding and skills in processing feed and livestock waste available in the environment, as well as supporting the independence of breeders in order to be able to optimize farm productivity through the utilization of integrated grazing land.